Evaluation of health-related knowledge, attitudes, and behaviors of undergraduate students by cardiovascular risk factors - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2021)
Aim: To determine the presence of cardiovascular (CV) risk (CVR) factors in university students and evaluate how these factors are affected from the knowledge, attitudes, and habits of the individuals regarding healthy lifestyle. Background: Starting from early ages, lifestyle habits such as lack of physical activity, unhealthy eating, and inappropriate drug use increase CV and metabolic risks of individuals. Methods: In April-May 2018, sociodemographic characteristics of 770 undergraduate students, in addition to their knowledge, attitudes, and habits regarding their nutrition and physical activity status were obtained through face-to-face questionnaires. CVR factors were determined according to blood pressure, blood glucose, total cholesterol levels, and anthropometric measurements. Collected data were compared by CVR factor presence (CV[+] or CV[-]) in students. Findings: The mean age of the participants was 22.3 +/- 2.6 years. 59.6% were female and 71.5% were students of non-health sciences. In total, 274 individuals (35.9%) belonged to CV(+) group (mean risk number: 1.3 +/- 0.5) with higher frequency in males (42.1% versus 31.6%, P < 0.05). The most common CVR factors were smoking (20.6%), high total cholesterol (7.5%), and hypertension/high blood pressure (6.0%). 15.5% of the participants regularly used at least one drug/non-pharmaceutical product. 11.3% complied the Mediterranean diet well. 21.9% of CV(+) stated consuming fast food at lunch compared to 14.3% of CV(-) (P < 0.05). 44.6% stated exercising below the CV-protective level. Conclusions: This study showed one-third of university students was at CVR, independent of their sociodemographic characteristics. Furthermore, the students appear to perform below expectations in terms of nutrition and physical activity. Extensive additional measures are needed to encourage young individuals for healthy nutritional and physical activity habits.
Keywords: cardiovascular risk; healthy lifestyle; smoking; young adult; COMMUNITY-BASED INTERVENTIONS; DIETARY-SUPPLEMENT USE; DISEASE; PREVENTION; PREVALENCE; COUNTRIES; PATTERNS; CHILDREN; SMOKING; HEART